Eksistensi Sekolah Islam Unggulan dalam Membangun Daya Saing Pendidikan Nasional - Arman; M. Nurul Humaidi (Civiliza Publishing, Indonesia., 2026)
This research aims to examine the existence of superior Islamic schools in strengthening the competitiveness of national education in the midst of the dynamics of globalization, technological developments, and the transformation of the modern education system. This study focuses on the role of leading Islamic schools in improving academic quality, building the religious character of students, and developing learning innovations and quality-oriented educational governance. The research uses a qualitative approach with the library research method through the analysis of various scientific sources in the form of journals, books, and previous research results that are relevant to Islamic education and educational competitiveness. The results of the study show that superior Islamic schools are able to build a competitive advantage through the application of an integrative curriculum that combines general knowledge with Islamic values holistically. In addition, strengthening religious culture, the use of digital technology in learning, the professionalism of educators, and visionary school leadership are strategic factors in improving the quality of Islamic educational institutions. The existence of superior Islamic schools also reflects the ability of Islamic education to respond to the demands of social change without ignoring the identity and spiritual values that are the main foundation of education. Thus, superior Islamic schools have an important contribution in producing human resources that are not only academically competitive, but also have moral integrity, adaptive abilities, and religious character that are relevant to the needs of national education in the era of globalization.